PENERAPAN STRATEGI MENGINGAT UNTUK MENINGKATKAN MEMORI SISWA SMP DENGAN MILD INTELLECTUAL DISABILITY - Muhammad Ikhsan; Tino Leonardi (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Intellectual disability is defined as a condition in which an individual experiences significant limitations in intellectual and adaptive functioning. Intellectual disability can be identified before an individual reaches the age of 18. The impact of these limitations is evident in the individual's ability to gather and retain information, leading to difficulties in various aspects of daily life and education. This study aims to evaluate the effects of implementing memory enhancement strategies in improving the memory capacity of female junior high school students with mild intellectual disability. The research methodology employed a single-case experimental design, where the subject's ability data was collected as a baseline measurement before the intervention, and then compared with the subject's ability after receiving the intervention. The intervention consisted of six sessions conducted once a week, with each session lasting two hours. The results of the intervention demonstrated a significant improvement in the subject's memory capacity compared to the baseline data before the intervention. Evaluation also indicated that the subject successfully achieved the targets set by the relevant authorities after experiencing an improvement in memory ability.